2015
DOI: 10.3390/ijms16024150
|View full text |Cite
|
Sign up to set email alerts
|

Major Peptides from Amaranth (Amaranthus cruentus) Protein Inhibit HMG-CoA Reductase Activity

Abstract: The objective of this study was to identify the major peptides generated by the in vitro hydrolysis of Amaranthus cruentus protein and to verify the effect of these peptides on the activity of 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMG-CoA reductase), a key enzyme in cholesterol biosynthesis. A protein isolate was prepared, and an enzymatic hydrolysis that simulated the in vivo digestion of the protein was performed. After hydrolysis, the peptide mixture was filtered through a 3 kDa membrane. The peptide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 25 publications
2
43
0
1
Order By: Relevance
“…Leaf extracts of A. spinosus singularly and in combination with vitamin C reversed unfavorable alterations (increased MDA but reduced GSH, CAT and SOD of heart) in adult rats on high fat diet [78]. Soares et al [79] cited in their work, three novel peptides from grain of A. cruentus, that significantly inhibited HMG-CoA reductase, a key enzyme in cholesterol biosynthesis; suggesting a possible hypocholesterolemic effect. Unprocessed and extruded amaranth hydrolysates (EAH) from A. hypochondriacus showed a reduction in the expression of interleukins involved in atherosclerosis in THP-1 lipopolysaccharide (LPS)-induced human macrophages.…”
Section: Cardioprotectivementioning
confidence: 99%
“…Leaf extracts of A. spinosus singularly and in combination with vitamin C reversed unfavorable alterations (increased MDA but reduced GSH, CAT and SOD of heart) in adult rats on high fat diet [78]. Soares et al [79] cited in their work, three novel peptides from grain of A. cruentus, that significantly inhibited HMG-CoA reductase, a key enzyme in cholesterol biosynthesis; suggesting a possible hypocholesterolemic effect. Unprocessed and extruded amaranth hydrolysates (EAH) from A. hypochondriacus showed a reduction in the expression of interleukins involved in atherosclerosis in THP-1 lipopolysaccharide (LPS)-induced human macrophages.…”
Section: Cardioprotectivementioning
confidence: 99%
“…Tachibana et al attributed that the hypolipidemic effect to the amino acid composition and sequence of the protein isolate, consistent with previous studies of legumes (Moriyama et al, 2004;Lovati et al, 2008). Inhibitory effects of natural (Pak et al, 2005: Soares et al, 2015 and synthetic (Lin et al, 2015;Pak et al, 2008aPak et al, , 2008bPak et al, , 2012 peptides on HMG-CoAr have been reported, but the underlying mechanism remained unclear. Marques et al (2015) and Lammi et al (2015) suggested that legume peptide inhibit HMG-CoAr via the interaction of these peptides with either the active site or NADH-binding site of the enzyme, thus preventing substrate binding to the enzyme and promoting endogenous cholesterol synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The change of HMG-CoA Reductase Activity [17] 1, 5, 25 or 125 μg/mL of β-Sitosterol, Oleanolic Acid, Emodin, Carotene, Resorcinol, Luteolin, α-L-Rhamnose, Pravastatin respectively were mixed into the reaction mixture for the HMGCoA activity detection. The reaction without HMG-CoA reaction substrate was incubated at 37°C, and absorbance was measured at 340 nm after 1 min and recorded as ΔA 1 Δt 1 .…”
Section: % =mentioning
confidence: 99%